Performance Design Futures 2022 -’Developing an academic Performance Design Curriculum in Cyprus’ - Antoniou, Klitsa (My University, 2026)
Performance Design Futures 2022 International academic symposium Organised by CYCSTAT, the Cyprus Centre of Scenographers and Theatre Architects and Technicians Theatro Polis OPAP Nicosia, Cyprus ‘’Developing an academic Performance Design Curriculum in Cyprus’’